The World on a globular projection. - D.F. Robinson & Co. (Hartford, Conn.) (1830)
Map shows world continents from the northern and southern hemispheres perspectives. Includes "A chart exhibiting the progress of Christianity from the birth of our Saviour to the present time." No scale noted.